THE EFFECT OF POLICY IMPLEMENTATION AND LEADERSHIP COMMITMENT ON THE SUCCESS OF LICENSING SERVICES - Teguh Muldiyanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Public services, especially licensing services in Kalideres Subdistrict, West Jakarta, are expected to contribute to community service, which in turn will be able to guarantee every community to obtain optimal service and not burden the community, especially for the lower middle class. Therefore, to optimize community service, many factors are needed, including policies and commitments themselves, because the implementation of policies and commitment of good leaders is believed to increase the success of a service. This research was conducted to analyze how much influence the implementation of policies and / or commitment of leaders both partially and jointly on the success of licensing services in Kalideres District, West Jakarta. This study uses an exploratory survey method that focuses on observation and the use of questionnaires to explore data from existing samples. It is expected that from this research, the implementation of policies and commitment of existing leaders can be measured and in the future it can be even better. Keywords: Policy implementation; leader commitment; licensing services; Kalideres West Jakarta